Kēsavadēv enṯe nityakāmukan : smaraṇa - Sītālakṣmi Dēv, 1945- (Sāhityapṟavarttaka Sahakaraṇasaṅghaṃ : Nāṣanal Bukksṯāḷ, 1981)
Reminiscences about her husband, P. Kesava Dev, b. 1905, Malayalam litterateur.